Construction of vinyl ester resins composite coatings via introducing silane-functionalized graphene oxide for enhancing comprehensive performance. (29th September 2022) - Li, Guidong; Fang, Heng; Hu, Yang; Chen, Xudong; Chu, Zhuangzhuang; Yang, Zhuohong
Abstract: Vinyl ester resins (VERs) are often used as anti-corrosive coating due to their high curing speed and good mechanical property in most industrial fields. However, many small holes can be formed during the curing process of these resins, resulting in they are not suitable for heavy anti-corrosion applications. Herein, approximately 100% utilization rate of raw materials and solvent-free polyfunctional acrylates (AGO-VERs) with excellent anti-corrosive properties are synthesized by crosslinking VERs with silane decorated graphene oxide (AGO) using toluene diisocyanate as the crosslinking agent. Compared with GO-VERs, AGO-VERs show better dispersibility and higher degree of peeling in the resin systems. Furthermore, the cured coating containing AGO-VER-6 exhibits the maximum tensile strength (80.73 MPa), flexural strength (178.58 MPa), Young's modulus (669.53 MPa) and impedance modulus (2.43 × 10 8 Ω cm 2 after soaking for 7 d). Finally, the possible corrosion protection mechanism of the modified VERs is clarified. Results demonstrate a simple and efficient approach for covalently combining VERs with GO well, which can achieve long-term corrosion protection of metal substrates in the field of heavy anti-corrosive coatings. Graphical abstract: Image 1 Highlights: 3-aminopropyltriethoxysilane-decorated graphene oxide (AGO) was synthesized. Composite coatings containing vinyl ester resins (VERs) and AGO were prepared. AGO exhibited good dispersibility in the resin systems. Composite coatings showed excellent mechanical properties and corrosion resistance.